Model Adaptasi Perdagangan Berjangka Komiditi Pertanian pada BMT dengan Menggunakan Akad Salam - Indah Rahma; Melati Fadla; Adinda Ayu Intan Cempakasari (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
AbstractThe adaptation futures contract model is the result of the adaptation of contact futures transactions conducted in the futures market, the Jakarta Futures Exchange (JFX). Then, the application is combined with one of the types of transactions in accordance with Islamic law in the field of agriculture, Salam. In practice, this model is expected to reach small-scale farmers in Indonesia who have problems in the availability of capital and access to markets (consumer).Nowadays the solution is needed to overcome the problems of both capital and market facing horticultural farmers. One of the financial institutions that reach out to the farming community is the Baitul Maal Wattamwil (BMT). Since the days of the Prophet Muhammad Islamic microfinance institutions have been there to function as a party (al-jihat), which handles all the property of the Muslims, either in the form of income and expenses. But over time, the complexity of the problems and needs of mankind in the economy continues to grow. This causes the function BMT continues to grow.This paper uses qualitative descriptive approach based on the study of literature or secondary data and subjective intuitive. After using both approaches, the futures contact adaptation model is equipped with a SWOT analysis. It aims to review models through four different sides. Keywords: BMT; SWOT analysis;